2020
DOI: 10.1101/2020.03.01.20029769
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The potential role of IL-6 in monitoring severe case of coronavirus disease 2019

Abstract: Background The outbreak of coronavirus disease 2019 in Wuhan City, China has spreads rapidly since December, 2019. Most patients show mild symptoms, but some of them develop into severe disease. There is currently no specific medication. The purpose of this study is to explore changes of markers in peripheral All rights reserved. No reuse allowed without permission. author/funder, who has granted medRxiv a license to display the preprint in perpetuity.

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
103
1
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(122 citation statements)
references
References 23 publications
(35 reference statements)
8
103
1
5
Order By: Relevance
“…Compared with non-ICU patients, ICU patients had higher plasma levels of IL2, IL6, IL7, IL10, GSCF, IP10, MCP1, MIP1A, TNFα, lactate dehydrogenase (LDH), ferritin and D-dimer. The number of lymphocytes was significantly reduced and C-reactive protein (CRP) was significantly increased in severe cases [10][11][12][13]. During the submission of this paper, several publications have also reported the analysis of antibody responses to N protein, S protein, and receptor-binding domain (RBD) on S protein in COVID-19 patients [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 95%
“…Compared with non-ICU patients, ICU patients had higher plasma levels of IL2, IL6, IL7, IL10, GSCF, IP10, MCP1, MIP1A, TNFα, lactate dehydrogenase (LDH), ferritin and D-dimer. The number of lymphocytes was significantly reduced and C-reactive protein (CRP) was significantly increased in severe cases [10][11][12][13]. During the submission of this paper, several publications have also reported the analysis of antibody responses to N protein, S protein, and receptor-binding domain (RBD) on S protein in COVID-19 patients [14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 95%
“…One potential therapeutic target is the IL-6 signaling pathway. IL-6 levels diverge profoundly between survivors and nonsurvivors in the third week after symptom onset and predict COVID-19 severity and in-hospital mortality (1, 8,11). Tocilizumab and sarilumab, monoclonal antibodies targeting the IL-6 receptor, and siltuximab, a chimeric antibody targeting IL-6, are currently being investigated for the treatment of patients with COVID-19-CSS (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23).…”
Section: Treating Cytokine Storm In Covid-19mentioning
confidence: 99%
“…Preventing cytokine storm syndrome in COVID-19 using α-1 adrenergic receptor antagonists Maximilian F. Konig, 1,2,3,4,5 Mike Powell, 6 Verena Staedtke, 7 Ren-Yuan Bai, 8 David L. Thomas, 9 Nicole Fischer, 5 Sakibul Huq, 8 Adham M. Khalafallah, 8 Allison Koenecke, 10 Ruoxuan Xiong, 11 Brett Mensh, 12 Nickolas Papadopoulos, 1,2,3 Kenneth W. Kinzler, 1,2,3 Bert Vogelstein, 1,2,3 Joshua T. Vogelstein,6 Susan Athey, 13 Shibin Zhou, 1,2,3 and Chetan Bettegowda 1,2,3,8 1 Ludwig Center, 2 Lustgarten Laboratory, and 3 Howard Hughes Medical Institute, Johns Hopkins Kimmel Cancer Center, Baltimore, Maryland, USA. 4 Division of Rheumatology, 5 Johns Hopkins University (JHU) School of Medicine, Baltimore, Maryland, USA.…”
mentioning
confidence: 99%
“…).Overall, elevations in IL-6 levels amongst patients with COVID-19 were identified in all included studies [33][34][35][36][37][38][39][40][41][42]. Multiple studies specifically identified higher levels of IL-6 amongst patients with more severe (complicated) disease.33,37-40 Descriptions of other inflammatory markers, including IL2R and ferritin, are contained in the Supplementary Appendix.…”
mentioning
confidence: 99%